2001
DOI: 10.1053/euhj.2001.2606
|View full text |Cite
|
Sign up to set email alerts
|

Stent design related neointimal tissue proliferation in human coronary arteries; an intravascular ultrasound study

Abstract: Coronary stent design has a significant impact on subsequent intimal hyperplasia after implantation into atherosclerotic human coronary arteries. The corrugated ring design of the Multi-Link stent proved to result in less tissue proliferation at 6-month follow-up than the tubular slotted design of Palmaz-Schatz and InFlow stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 20 publications
0
23
0
3
Order By: Relevance
“…The simulation technique predicted the same ranking of stents based on average neointimal area as two clinical studies (Hoffmann et al, 2001;Kastrati et al, 2001) with the open-cell-type stent outperforming more rigid stents. Simulations predicted less of a difference between the PALMAZ and NIR stent than between the MULTILINK and PALMAZ stent, in terms of both tissue volume and cell numbers.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The simulation technique predicted the same ranking of stents based on average neointimal area as two clinical studies (Hoffmann et al, 2001;Kastrati et al, 2001) with the open-cell-type stent outperforming more rigid stents. Simulations predicted less of a difference between the PALMAZ and NIR stent than between the MULTILINK and PALMAZ stent, in terms of both tissue volume and cell numbers.…”
Section: Discussionmentioning
confidence: 98%
“…We applied the simulation technique in 3D to three stents similar in design to the ones analysed clinically by Hoffmann et al (2001) and Kastrati et al (2001). If the hypothesis is corroborated, then this methodology could be applied to future device design and treatment options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] On the basis of these risk factors, patients enrolled in both nonrandomized studies and clinical trials have been classified as having a high, intermediate, or low risk of restenosis. Therefore, the binary restenosis rates (Ͼ50% diameter stenosis angiographically) and major adverse cardiac event (MACE) rates in human studies vary greatly depending on the overall risk profile of patients enrolled in these studies.…”
Section: Human Studiesmentioning
confidence: 99%
“…23,24) Studies showed the significant impact of stent design on restenosis rates, [25][26][27][28] and patterns of neointimal hyperplasia. 29,30) One important observation is the lower rates of TLR and binary restenosis in both groups, including a much lower rate among CCS in comparison to the impression of the huge difference between DES and BMS in the randomized trials. This finding was reported by some studies, 6) still one study showed no significant clinical difference, even in revascularization between DES and CCS.…”
Section: Figurementioning
confidence: 99%